Pengaruh Ekuitas Merek Terhadap Preferensi Rasa Kopi Starbucks - Theresia Theresia; Cokki Cokki (Jurnal Manajerial Dan Kewirausahaan, 2019)
This study examines the effect of brand equity on Starbucks’ coffee taste preference. The design of this research is experiment. The sampling technique used convenience sampling. Participants are 53 undergraduate students of Faculty of Economics of Tarumanagara University in Jakarta. The treatment used is 50 mililiters Starbucks’ coffee. Data were collected using questionnaire. The analysis used PLS-SEM. The result of this study indicates that Starbucks’ coffee taste preference on blind tests are different from Starbucks’ coffee taste preference on non-blind tests and Starbucks’ brand equity has positive effect on Starbucks’ coffee taste preference.Penelitian ini meneliti pengaruh variabel ekuitas merek terhadap preferensi rasa kopi Starbucks. Desain penelitian ini adalah eksperimen. Teknik pengambilan sampel menggunakan convenience sampling. Partisipan adalah 53 mahasiswa Fakultas Ekonomi Universitas Tarumanagara di Jakarta. Perlakuan yang digunakan adalah 50 mililiter kopi Starbucks. Teknik pengambilan data menggunakan kuesioner. Analisis yang digunakan adalah PLS-SEM. Hasil penelitian ini menunjukkan bahwa preferensi rasa kopi Starbucks pada blind test tidak sama dengan preferensi rasa kopi Starbucks pada non-blind test dan ekuitas merek Starbucks berpengaruh positif terhadap preferensi rasa kopi Starbucks.